HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN MOTIVASI BELAJAR SISWA SMA X LAMPUNG BARAT SELAMA PANDEMI COVID-19 - Setriani Setriani; Meilia Ishar; Fatimah Zahra (Universitas Muhammadiyah Lampung, 2021)
ABSTRACTMotivation is the driving force that moves a person's soul, encouraging someone to develop themselves and mobilize all the abilities and energy they have in order to achieve maximum performance. The purpose of this study was to determine whether there was a relationship between peer support and learning motivation of X high school students in West Lampung during the pandemic. One that affects student learning motivation is the existence of social support from peers, peers have an important role in adolescent development, especially at the stage of learning development where adolescents who have many friends will be able to increase interest in their education. The sample of this study amounted to 118 students in grades 1 and 2 of high school. people with the data analysis method used is the Pearson Product Moment correlation method. The results of the correlation coefficient value of the correlation coefficient of 0.685 indicate a relationship between the variables of peer social support on student motivation during the Pandemic. Keywords: social support, learning motivation, pandemic, peers ABSTRAKMotivasi belajar merupakan daya penggerak yang memotivasi semangat seseorang, mendorong seseorang untuk mengembangkan diri dan menggerakkan semua kemampuan serta energi yang dimilikinya demi mencapai prestasi yang maksimal. Tujuan penelitian adalah untuk mengetahui apakah ada hubungan antara dukungan teman sebaya dengan motivasi belajar siswa SMA X di Lampung Barat selama masa Pandemi. Salah satu yang mempengaruhi motivasi belajar siswa adalah adanya dukungan sosial dari teman sebaya. Teman sebaya memiliki peran penting dalam perkembangan remaja terutama pada tahapan perkembangan belajar dimana remaja yang banyak memiliki teman akan mampu meningkatkan minat terhadap pendidikannya. Sampel penelitian ini berjumlah 118 siswa kelas 1 dan 2 SMA dengan metode korelasi Pearson Product Moment. Hasil koefisien korelasi sebesar 0.685 menunjukan adanya hubungan positif antara variabel dukungan sosial teman sebaya terhadap motivasi belajar siswa dimasa pandemi. Kata kunci: dukungan sosial, motivasi belajar, pandemic, teman sebaya